#### Answer

FALSE

#### Work Step by Step

As we know
$f_{xy}=(f_{x})_{y}=\frac{∂}{∂y}(\frac{∂f}{∂x})$
Hence, the statement is false.

Published by
Brooks Cole

ISBN 10:
0-53849-787-4

ISBN 13:
978-0-53849-787-9

FALSE

As we know
$f_{xy}=(f_{x})_{y}=\frac{∂}{∂y}(\frac{∂f}{∂x})$
Hence, the statement is false.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.